2015
DOI: 10.1016/j.egja.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative urinary retention after general and spinal anesthesia in orthopedic surgical patients

Abstract: Background: After general, spinal anesthesia and surgery, urinary retention is common. The aim of the study was to compare the effect of general anesthesia versus spinal anesthesia on postoperative urinary retention Patients and methods: After obtaining local ethics committee approval and written consent, 60 male patients, aged 16-40 years, ASA -physical status I and II were divided into two groups (S) 40 patients and (G) 20 patients undergoing surgery of the lower limb lasting up to 90 min (knee arthroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This lack of criteria to diagnose UR and, therefore, to indicate BRC, contributes to the great variability in the incidence rates of UR described in the literature. Several studies (7)(8)(9)(18)(19)(20) report incidence rates ranging from 2% to 60%, which is consistent with those we found when assessing incidence in the categories suggested in the literature (< 300mL, from 300 mL to 499 mL, and ≥ 500 mL). However, the incidence rates found in the literature come from studies predominantly conducted with patients in the immediate postoperative period or admitted to post-surgical units.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This lack of criteria to diagnose UR and, therefore, to indicate BRC, contributes to the great variability in the incidence rates of UR described in the literature. Several studies (7)(8)(9)(18)(19)(20) report incidence rates ranging from 2% to 60%, which is consistent with those we found when assessing incidence in the categories suggested in the literature (< 300mL, from 300 mL to 499 mL, and ≥ 500 mL). However, the incidence rates found in the literature come from studies predominantly conducted with patients in the immediate postoperative period or admitted to post-surgical units.…”
Section: Discussionsupporting
confidence: 89%
“…The literature on the theme is almost exclusively limited to studies with surgical patients, mainly in the immediate post-anesthesia period. In this context, the incidence of UR ranges from 2% to 60% and is especially related to the type of surgery performed, the type of anesthesia administered, and the use of anticholinergic or analgesic drugs (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, the authors of a recent meta-analysis [4] found that the duration of catheterization may influence POUR and stated that a duration of 24-48 hours in those with risk factors for POUR is a reasonable option to reduce its occurrence. Furthermore, the anesthetic type and use of continuous epidural analgesia did not influence POUR, which is similar to prior results [14], but overall controversial [12,15]. Bladder hypotonia is expected to resolve within 8 hours after discontinuation of spinal anesthesia [5], so it is not surprising that no difference in observed urinary retention was observed in our study, which had a minimum of 13.9 hours of urinary catheterization.…”
Section: Discussionsupporting
confidence: 86%
“…The risk to be catheterized after hyperbaric bupivacaine and articaine was eight times and three times higher, respectively, as compared to general anesthesia. Available literature comparing general anesthesia with spinal anesthesia and its association with urinary catheterization is limited (Bjerregaard et al, 2015;Fernandez et al, 2014;Niazi & Taha, 2015;Scholten et al, 2018). More specifically, there are no recent studies regarding POUR or urinary catheterization after general anesthesia, let alone comparing their incidence with spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%